Description of Calcium Oxalate Crystals in Urine Based on Degree of Dehydration - Syamsinar, Syamsinar; Aryandi, Rahmat; AB, Azsrul; Islawati, Islawati (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
Dehydration is a condition of lack of body fluids because the amount that comes out is more than the amount of fluid that goes in, water output must be balanced with water intake, if there is an imbalance of fluids in the body, dehydration will occur. Reducing fluid consumption means the body will automatically experience dehydration, this dehydration will trigger a constant decrease in urine volume. Urine volume indicates insufficient water in the body dissolving minerals and urine. If there is not enough fluid in the urine, the bound oxalate and calcium will collect and form stones. The formation of stones is directly related to lack of fluid intake in the body. The formation of calcium oxalate crystals can cause kidney stones. Oxalate can precipitate and form calcium oxalate which cannot be absorbed by the body, resulting in insoluble salt deposits forming which cause kidney disease. In the body, oxalate will combine with calcium to form calcium oxalate crystals. To determine the appearance of calcium oxalate crystals in urine, the degree of dehydration. This type of research is qualitative research using the microscopic method. The population in this study were students, etc. Medical laboratory technology, Stikes Panrita Husada Bulukumba. There were 45 samples, 15 samples of mild dehydration, 15 samples of moderate dehydration, and 15 samples of severe dehydration. The sample in this study was a urine sample. Based on the research that has been carried out, results were obtained from 45 samples, 15 samples of mild dehydration, 15 samples of moderate dehydration, and 15 samples of severe dehydration. In severe dehydration, 1 sample was found that obtained a positive result (+) with a percentage of (6.7%).